2022
DOI: 10.1111/irv.13062
|View full text |Cite
|
Sign up to set email alerts
|

Comparative hospitalization risk for SARS‐CoV‐2 Omicron and Delta variant infections, by variant predominance periods and patient‐level sequencing results, New York City, August 2021–January 2022

Abstract: Background: Comparing disease severity between SARS-CoV-2 variants among populations with varied vaccination and infection histories can help characterize emerging variants and support healthcare system preparedness. Methods:We compared COVID-19 hospitalization risk among New York City residents with positive laboratory-based SARS-CoV-2 tests when ≥98% of sequencing results were Delta (August-November 2021) or Omicron (BA.1 and sublineages, January 2022). A secondary analysis defined variant exposure using pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Comparatively lower fatality risk in hospitalized COVID-19 patients infected with the ancestral strain or Omicron than Delta were reported in unvaccinated individuals from the UK and the US [15-18].…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively lower fatality risk in hospitalized COVID-19 patients infected with the ancestral strain or Omicron than Delta were reported in unvaccinated individuals from the UK and the US [15-18].…”
Section: Discussionmentioning
confidence: 99%
“…An England cohort study supported our findings that confirmed Omicron cases had a lower risk of hospital admission and any hospital attendance compared to Delta cases ( 67 ). Greene et al ( 79 ) founded the risk of hospitalization was lower for New York patients who tested positive for Omicron than for those who tested positive for Delta.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that the average fecal viral shedding rate for hospitalized individuals (who have an average recovery period of 8 days [80]) is the same (i.e., ζ H = ζ I = 4.49 × 10 7 viral RNA per gram). Admittedly, it is an extremely crude way of approximating ζ H , however since the proportion of individuals who are in H class is a small fraction of that in I [81], the impact of this crude assumption is negligible on the overall viral concentration in wastewater. Similarly, the average fecal viral shedding rate for recovered individuals who are still shedding (i.e., individuals in J compartment), denoted as ζ J , is: The value of the parameter ζ J , obtained from Equation 3.2, is significantly lower than that of ζ I given in Table 3), suggesting that viral shedding recovered individuals shed at a rate that is significantly lower than that of infectious individuals.…”
Section: Data-fitting and Parameter Estimationmentioning
confidence: 99%